The effect of dutasteride on microscopic and macroscopic changes of testosterone replacement treatment on prostate tissue. (19th July 2018) - Diri, Mehmet Akif; Diri, Banu; Yildiz, Levent; Büyükalpelli, Recep
Abstract: Testosterone replacement therapy has a growing interest in daily practice; however, debates on its safety for prostate cancer still continue. Dutasteride—a 5α‐reductase inhibitor—was shown to be effective in preventing prostate cancer. We therefore aimed to evaluate the effect of testosterone replacement therapy and dutasteride treatment on prostate tissue in castrated rats. Rats were randomised in four groups after bilateral orchidectomy as follows: Group I received testosterone + dutasteride, Group II received only testosterone, Group III had no medical treatment, and Group IV was the control group. After 3 months, rats were sacrificed and laboratory and histopathological examinations were performed. In Groups I and II, prostate volume, T and DHT levels were significantly higher compared to Group III and controls. Groups I and II had also significantly greater preneoplastic histopathological signs; however, in intergroup analyses, Group I showed less premalignant changes compared to Group II. We concluded that dutasteride was effective when combined with testosterone therapy in preventing premalignant histopathological changes in prostate tissue. Further evidence is needed to confirm our findings.